Influence of beta-lactam antibiotics and ciprofloxacin on cell envelope of Escherichia coli. - Suerbaum, S (1987)
The effects of subinhibitory concentrations of different beta-lactam antibiotics and one quinolone on the quantitative composition of the outer membrane (OM) of two strains of Escherichia coli, on lipid translocation into the OM, and on the production of capsular K1 polysaccharide were studied. The phospholipid/amino acid ratio was reduced in almost all OM preparations from antibiotic-treated bacteria. In one strain, antibiotic treatment increased the lipopolysaccharide/amino acid ratio. The amount of peptidoglycan fragments bound to the OM was increased by all the antibiotics. In pulse-chase experiments with a radioactive lipid precursor, ciprofloxacin, imipenem, and aztreonam inhibited phospholipid translocation into the OM. Furthermore, imipenem, cephaloridine, and ciprofloxacin induced a pronounced reduction of the production of capsular K1 polysaccharide. Thus, antibiotics seem to induce marked changes of the quantitative composition of the cell envelope of E. coli. Possible connections of these data with findings on the influence of antibiotics on functional parameters of the host-parasite relationship such as OM immunogenicity and serum resistance are discussed.